Gender, microentrepreneurship, human flourishing: Exploring the experiences of women sari-sari store owners toward inclusive growth - Diana Roldan Rueda; Eylla Laire M. Gutierrez (Philippine Institute for Development Studies (PIDS), 2024)
For years now, women's involvement in entrepreneurial activities has been widely advocated as part of economies' developmental agenda. This is evidenced by the numerous initiatives, projects, and roadmaps that promote women's integration in economic activities through entrepreneurship. Underpinning these efforts is an assumption that women's active participation to economic activities result to their improved well-being and empowerment. While this is an essential step to improve women's conditions, their realities prove to be more complex. Beyond the economic contributions of such entrepreneurial activities to women, other facets (i.e., psychological, social, political, among others) need to be accounted for as well. As such, this study primarily answered the question: "How does women's engagement in micro-enterprising facilitate their own and their communities' human flourishing and empowerment?" More specifically, the study examined the critical role of sari-sari stores in the socio-economic landscape of the Philippines, particularly focusing on their contributions to community development and women's flourishing and empowerment. While sari-sari store owners often face financial constraints, this research highlights a significant relationship between micro-entrepreneurship, human flourishing, and empowerment. Through the analysis of Flourishing Index (FI) and Secured Flourishing Index (SFI) measures and the Empowerment Model, the findings revealed that the women sari-sari store owners exhibit high levels of well-being, empowerment, optimism, and resilience, despite limited economic prosperity. The study further explored how sari-sari stores serve not only as micro-retail enterprises but also as platforms for fostering individual and social well-being. That is, the women were found to exhibit psychological and social empowerment through their ownership of sari-sari stores, while their economic and political empowerment proved to be a work in progress. The results of the study suggest that women, through their ownership of sari-sari stores, are able to achieve individual well-being while also extending it to their own communities. Thus, this study offered a nuanced perspective on the significance of sari-sari stores, not only to the economic development of communities, but the individual and social well-being of its women owners.
Keywords: 330; micro-entrepreneurship; female leadership; women empowerment; human flourishing